Kedudukan dan Tanggung Jawab POLRI dalam Penggunaan Senjata Api untuk Melumpuhkan Pelaku Kejahatan - Adiesta Zuhdi Rifki Ma’ruf; Hanuring Ayu; Nourma Dewi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The use of firearms by the Indonesian National Police (Polri) to incapacitate criminals constitutes an exercise of state authority in maintaining public security and order. However, their use often raises legal concerns regarding the limits of police authority, the protection of human rights, and the legal accountability of officers. This study aims to analyze the position of Polri in the use of firearms and to examine the forms of legal responsibility arising from the abuse of such authority.This research employs a normative legal method using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively. The study focuses on relevant regulations, including Law Number 2 of 2002 concerning the Indonesian National Police, regulations governing the use of force in police actions, and human rights principles in law enforcement. The findings show that the authority to use firearms is an attributive power granted by law to support Polri’s functions of protection, public service, and law enforcement. Firearms may only be used in specific situations as a measure of last resort (ultimum remedium), while adhering to the principles of legality, necessity, proportionality, and accountability. Responsibility for misuse may involve administrative, criminal, and civil liability. Strengthening oversight, improving professionalism, and refining regulations are essential to balance effective law enforcement with human rights protection.